Bipartite entanglement extracted from multimode squeezed light generated in lossy waveguides - Kopylov, Denis; Meier, Torsten; Sharapova, Polina R. (APL Quantum)
Entangled two-mode Gaussian states constitute an important building block for continuous variable quantum computing and communication protocols. In this work, we theoretically study two-mode bipartite states, which are extracted from multimode light generated via type-II parametric downconversion (PDC) in lossy waveguides. For these states, we demonstrate that the squeezing quantifies entanglement and we construct a measurement basis, which results in the maximal bipartite entanglement. We illustrate our findings by numerically solving the spatial master equation for PDC in a Markovian environment. The optimal measurement modes are compared with two widely used broadband bases: the Mercer–Wolf basis (the first-order coherence basis) and the Williamson–Euler basis.

How Much to Pay for Tax Certainty? The Role of Advance Tax Rulings for Risky Investment under Loss Offset and Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren
This study examines the impact of tax certainty through advance tax rulings (ATRs) on firms' risky investments under cash flow and tax uncertainty. Both firms and governments have expressed growing concern about increasing tax uncertainty, due to frequent tax reforms and the difficulty in applying ambiguous tax laws and anticipating audit outcomes. One remedy is the provision of ATRs, which offer upfront clarification of tax issues to reduce tax uncertainty and increase risk-taking. We analyze how these uncertainties, along with different tax rates, loss offset provisions, and ATR fees affect investment strategies. Our results suggest, first, that ATRs encourage riskier investments, particularly in tax regimes with generous loss offsets. We identify optimal ranges of ATR fees that benefit firms and tax authorities. Second, we show that it may be beneficial to design ATRs with a low or negative fee. Third, our study reveals a U-shaped relationship between firms' risk aversion and their willingness to pay for tax certainty, with willingness being higher for firms at low or high levels of risk aversion. In contrast, moderately risk-averse firms are only willing to accept low fees. Overall, our results highlight the importance of low-cost tax certainty combined with generous loss offset provisions to encourage risky investments.

Civic Statistical Literacy: Konzept und praxisnahe Umsetzung am Beispiel des Klimawandels - Biehler, Rolf; Engel, Joachim; Frischemeier, Daniel; Podworny, Susanne (mathematica didactica)

Development of an Effector-Specific Stop Signal Task with Higher Complexity: A Proof-of-Concept Study - Piskin, Daghan Yüksel; Gokeler, Alli; Chen, Yin-Hsuan; Baumeister, Jochen (Journal of Motor Behavior)

Exergaming Rejuvenates Resting-State Brain Complexity and Modulates Adaptability During Gameplay in Older Adults: An EEG Multiscale Entropy Study - Piskin, Daghan Yüksel; Müller, Helen Martha; Nina Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Skilled passing in football may regress following an anterior cruciate ligament injury as a result of cortical changes: preliminary EEG evidence - Piskin, Daghan Yüksel; Cobani, Gjergji; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen

Describing the nub in maximal Kac-Moody groups - Bischof, Sebastian; Marquis, Timothée
Let $G$ be a totally disconnected locally compact (tdlc) group. The contraction group $con(g)$ of an element $g\in G$ is the set of all $h\in G$ such that $g^n h g^{-n} → 1_G$ as $n → ∞$. The nub of $g$ can then be characterized as the intersection $nub(g)$ of the closures of $con(g)$ and $con(g^{-1})$. Contraction groups and nubs provide important tools in the study of the structure of tdlc groups, as already evidenced in the work of G. Willis. It is known that $nub(g) = \{1\}$ if and only if $con(g)$ is closed. In general, contraction groups are not closed and computing the nub is typically a challenging problem. Maximal Kac-Moody groups over finite fields form a prominent family of non-discrete compactly generated simple tdlc groups. In this paper we give a complete description of the nub of any element in these groups.

On flat groups in affine buildings - Bischof, Sebastian
In this article we work out the details of flat groups of the automorphism group of locally finite Bruhat-Tits buildings.

Mündliche Prüfungen im Mathematikunterricht – welche Arten des Wissens werden abgefragt? - Hellmund, Johannes (Beiträge zum Mathematikunterricht 2025)
Prüfungen sind ein wesentlicher Bestandteil des Mathematikunterrichts. Mündliche Prüfungsformate sind insbesondere in Abschlussprüfungen üblich, wurden aber bislang kaum untersucht. Dieses Projekt widmet sich dem Vorkommen und der Bedeutung verschiedener Wissensarten in mündlichen Prüfungen. Dazu soll auf Grundlage videografierter Prüfungsgespräche eine Taxonomie für abgefragte Wissensarten entwickelt werden. Der Vortrag präsentiert die Konzeption sowie erste Ergebnisse einer Vorstudie, die als Basis für eine vertiefte Analyse realer Prüfungen dient.

Tree-Based OWL Class Expression Learner over Large Graphs - Demir, Caglar; Yekini, Moshood Olawale; Röder, Michael; Mahmood, Yasir; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)

Robustness Evaluation of Knowledge Graph Embedding Models Under Non-targeted Attacks - Kapoor, Sourabh; Sharma, Arnab; Röder, Michael; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)

Link Prediction Under Non-targeted Attacks: Do Soft Labels Always Help? - Memariani, Adel; Röder, Michael; Sharma, Arnab; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)

Explainable Benchmarking through the Lense of Concept Learning - Zhang, Quannian; Röder, Michael; Srivastava, Nikit; KOUAGOU, N'Dah Jean; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference 2025)

„Endloskassetten im eigenen Kopf“ – Kindheits- und Jugendtopografien während der Flucht aus der Deutschen Demokratischen Republik in Post-DDR-Jugendromanen seit 2010. - Jagdschian, Larissa Carolin (Kinder- und Jugendliteratur in der DDR)

More money or better procedures? Evidence from an Energy Efficiency Assistance Program - Chlond, Bettina; Goeschl , Timo; Kesternich, Martin (Journal of Environmental Economics and Management)

Bedürfnisse von Lehrkräften zu digitalen Medien adressieren! - Weiler, David; Burde, Jan-Philipp; Costan, Kasim; Große-Heilmann, Rike Isabel; Kulgemeyer, Christoph; Lässer, Armin; Riese, Josef; Schubatzky, Thomas (Lernen, lehren und forschen im Schülerlabor. Gesellschaft Für Didaktik Der Chemie Und Physik Jahrestagung 2024 in Bochum)

UniQ-Gen: Unified Query Generation Across Multiple Knowledge Graphs - Vollmers, Daniel; Srivastava, Nikit; Zahera, Hamada Mohamed Abdelsamee; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Knowledge Engineering and Knowledge Management)
Generating SPARQL queries is crucial for extracting relevant information from diverse knowledge graphs. However, the structural and semantic differences among these graphs necessitate training or fine-tuning a tailored model for each one. In this paper, we propose UniQ-Gen, a unified query generation approach to generate SPARQL queries across various knowledge graphs. UniQ-Gen integrates entity recognition, disambiguation, and linking through a BERT-NER model and employs cross-encoder ranking to align questions with the Freebase ontology. We conducted several experiments on different benchmark datasets such as LC-QuAD 2.0, GrailQA, and QALD-10. The evaluation results demonstrate that our approach achieves performance equivalent to or better than models fine-tuned for individual knowledge graphs. This finding suggests that fine-tuning a unified model on a heterogeneous dataset of SPARQL queries across different knowledge graphs eliminates the need for separate models for each graph, thereby reducing resource requirements.

Otfried Preußlers Lyrik während der Kriegsgefangenschaft im Zweiten Weltkrieg - Jagdschian, Larissa Carolin (Otfried Preußler)

Dystopien im fortgeschrittenen Englischunterricht: Station Eleven und The Wall - Hohwiller, Peter (Impulsgeber Fremdsprachen. Best Practice und Diskussionen aus der Tagung des "Gesamtverbands Moderne Fremdsprachen Bayern")

Great Britain in nine short stories